UPAYA MENINGKATKAN KETERAMPILAN MENULIS CERPEN DENGAN MENGGUNAKAN METODE IMAGE STREAMING (Pengaliran Bayangan) - Nurul Hasanah (JURNAL SASTRA INDONESIA (SASINDO), 2012)
Method of Image Streaming (jetting shadow), an activity to let the shadows come and appear before the eyes of your mind. But do not consciously decide the content of these images. And while you view the images, describe aloud to an external focus (tape recorder or listener) the content of these images in detail (Wenger, 2011: 308). Image Streaming (drainage shadow) connects directly powers the verbal conscious mental powers are much richer, smoother, and more thorough. These resources more quickly and easily into private property and those who are rich and insightful eventually become part of an ongoing conscious perception. Drainage of the shadow caused some parts of the brain and mind work together more closely. This integration build balance, strengthen the weak points and to quickly increase the strength of intellectual child.